Positronium atom scattering by H-2 in a coupled-channel framework - Biswas, P. K.; Adhikari, S. K. (Iop Publishing Ltd, 2000)
The scattering of ortho-positronium (Ps) by H-2 has been investigated using a three-Ps-state (Ps(1s,2s, 2p)H-2(X (1)Sigma(g)(+))) coupled-channel model and using the Born approximation for higher excitations and ionization of Ps and B (1)Sigma(u)(+) and b (3)Sigma(u)(+) excitations of H-2. We employ a recently proposed time-reversal-symmetric non-local electron-exchange model potential. We present a calculational scheme for solving the body-frame fixed-nuclei coupled-channel scattering equations for Ps-H-2, which simplifies the numerical solution technique considerably. Ps ionization is found to have the leading contribution to target-elastic and all target-inelastic processes. The total cross sections at low and medium energies are in good agreement with experiment.